1 - Peace and Democracy in Mozambique: An Endless Transition - Bussotti, Luca (Africa Development, 2021)
Mozambique has long been considered a political success story in Africa. Nevertheless, it was clear from the signing of the General Peace Agreement in 1992 and the first general elections in 1994 that the official narrative of this success hid severe problems. The major challenge for Mozambican democracy has been the management of the electoral process. With little transparency and not much evidence of legal process, the consequence has been the repeated resurgence of political tensions and military clashes between Renamo and the Frelimo-led national Government. This paper seeks to explore the relationship between ‘negative peace’ and the lack of transparency in Mozambican electoral processes, whose main consequence is an ‘endless transition’ towards a ‘normal’ model of democracy.